English Language Competence of Secretary Students through Report Writing: Corpus Based Study - Elvi Citraresmana (TEKNOSASTIK, 2018)
This research is entitled “English Language Competence of Secretary Students through Report Writing:Corpus Based Study”. The main purpose of this research is to analyze the language competence of the Secretary Students in one of popular Academy Secretary in Bandung. The Language competence is something important for students in order to understand what they say or what they write. Every language competence implies meanings. Unfortunately not all students know how to understand the meanings through language. What they have in their minds that they have to write in good grammatical patterns. They keep busy memorizing the grammatical patterns without knowing the purpose of those patterns. This research uses the Corpus Linguistics method. This newly method is quite promising and interesting to implement in this research. The definition of Corpus Linguistics is used the theories which was proposed by McEnery and Wilson (1996,2001), Sinclair et al. (2004), Lindquist (2009), McEnery and Hardie (2012). In collecting data, the writer determined the keywords then found out the implementation of those words into their writing. There are 7 key words which are used by the students frequently. The result of this research shows that the students mostly use the elements of grammar such as determiner of “the” and “a”, preposition such as “in”, “on”, “about”; yet, they rarely implement those 7 keywords with any variation. Lack of using variation collocation to the keywords causing the ambiguity to the readers.   Keywords: corpus linguistics, language competence, secretary, grammar, pattern